Análisis de la burocracia, temas de reflexión - Soria Freire , Vladinir (Revista Universidad de Guayaquil, 2002)
The workers of the public sector (the bureaucrats) have been perceived by the society like uncooperative and inefficientpeople, so much that so the neoliberalism proposed by such reason the reduction of the size of the State. The problem with thebureaucracy is the weak institutionality, which generates Incentives for the corruption, when existing a combination of reasons,opportunities and impunity. If the society wants to eliminate the corruption in the public sector, it should stop supporting the political clientelism and should guide its efforts toward a social controllership of the public resources. These principles should figure in legal innovations, so much in the Law of elections as in the Law of Civil Service (LOSCCA).
Keywords: corruption; citizen participation; LOSCCA